KONDISI RUMAH PENDERITA TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS SUMBERSARI KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Paundanan, Matius; Rikwan; Pelima, Robert V.; Angelin Putri Seya (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
Data from the Parigi Moutong District Health Service states that the number of Tuberculosis cases in Parigi Moutong District continues to increase every year. In 2022 the number of TB cases will increase even more with the number of cases of 810 pulmonary tuberculosis sufferers in the Parigi Moutong District area). The aim of the research was to determine the condition of the homes of pulmonary tuberculosis sufferers in the working area of the Sumbersari Community Health Center, South Parigi District, Parigi Moutong Regency. This type of research is quantitative research with a descriptive approach. The research was carried out in the working area of the Sumbersari Health Center, South Parigi District, Parigi Moutong Regency, the research variables were ventilation, residential density, house floors, walls and ceilings. Data collection uses a questionnaire. The sam-ple used a total sampling of 9 people. Based on the results of univariate analysis, the ventilation conditions in most respondents' homes meet the requirements. Condition: Most of the house occupancy densities meet the requirements. The condition of the walls of the house all meet the requirements. Most of the house floor condi-tions meet the requirements. The condition of most house ceilings does not meet the requirements. The conclu-sion of the research is that the condition of tuberculosis sufferers' houses in terms of ventilation, density of the house, walls, floor and ceiling mostly meets the requirements. Suggestions for the quality of service for patients suffering from tuberculosis. Sumbersari Community Health Center needs